Rancang Bangun Aplikasi Sistem Pendukung Keputusan Promosi Jabatan dengan Menggunakan Metode Profile Matching pada PT. Lintech Duta Pratama - Rohmansyah, Mochamad Imam Mahudi; Sukmaaji, Anjik; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
The promotion of Employee Position at PT Lintech Duta Pratama Surabaya is still done manually, so it does not close the possibility if the decision making is done subjectively by only looking at certain aspects, in the selection of employees who only see from the mass of the lingering work that assumes it must be more competent is not effective. Looking at the existing problems, a Decision Support System (SPK) is needed that can help solve problems in decision making by adjusting the criteria and weights that have been determined by the company. The method used in decision making is the Profile Matching method. With this method we can find out the employees who fall under the weights and criteria of promotion of positions at PT. Lintech Duta Pratama Surabaya. There is a problem with PT. Lintech Duta Pratama Surabaya needs a decision support system in determining the promotion of employee positions. The system development method uses a waterfall model which is a systematic and skuensial software development that will be built using the Laravel Framework, PHP, and MySQL database programming languages. The final result in this research is the making of a Decision Support System for The Promotion of Employee Positions at PT. Lintech Duta Pratama Surabaya with Profile Matching method based on this Website can determine employees who deserve to be considered and have not been selected to choose one of the best in occupying the position. After the decision obtained in the application of the decision support system, the system will display a list of prospective employees who can be balanced to be an option in the promotion of office.